Potensi Sekretom Mesenchymal Stem Cell pada Terapi Regeratif Penyakit Paru Fibrosis - Kartika, Ronald Winardi; Timotius, Kris Herawan (Jurnal MedScientiae, 2024)
Fibrosis lung diseases such as chronic obstructive pulmonary disease, acute lung injury and post-Covid 19 fibrosis lung disease are considered as major health problems in the last decade. Cellular therapy with Mesenchymal Stem Cells (MSC) offers a novel therapeutic approach for fibrosis lung disease associated with anti-inflammatory, immunomodulatory, regenerative, pro-angiogenic and anti-fibrotic properties. Such therapeutic effects may be attributed to the MSC-secretome, which is made of free soluble proteins and extracellular vesicles (EVs). This review summarises some recent literature findings related to the efficacy and safety of MSC-derived products in pre-clinical models of lung diseases, demonstrating the biologically active substances contained in the MSC-secretome and its mechanisms involved in tissue regeneration. A perspective view is given on the secretome being a high-quality, safe and effective medicinal product,